2003
DOI: 10.1271/bbb.67.1888
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Two Isoforms of Glucose 6-Phosphate Dehydrogenase (G6PDH) fromChlorella vulgarisC-27

Abstract: Two kinds of isoforms of glucose 6-phosphate dehydrogenase (G6PDH) were purified from cells of a freezing-tolerant strain, Chlorella vulgaris C-27, by sequential steps of chromatography on five kinds of columns, including a HiTrap Blue column which showed excellent separation of the isoforms from each other. The two isoforms (G6PDH1 and G6PDH2) were purified up to 109-fold and 197-fold with specific activity of 14.4 and 26.0 U/mg-protein, respectively. G6PDH1 showed an apparent Mr of 200,000 with a subunit Mr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Studies about regulation of G6PD has been carried out in plants, eukaryotic algae and cyanobacteria but glucose-6phophate dehydrogenase encoding gene has been isolated from only few of these sources (Srivastava and Anderson, 1983;Fickenscher and Scheibe, 1986;Graeve, Schaewen and Scheibe, 1994;Gleason, 1996). Two isoforms (cytosolic and chloroplastic isoforms) of G6PD has been reported in green algae Chlorella vulgaris C-27 (Honjoh et al, 2003). Several isoforms of G6PDH have been reported in cytosol, plastidic stroma, and peroxisomes of higher plants (Corpas et al, 1998).…”
Section: Distribution Of Glucose-6-phosphate Dehydrogenasementioning
confidence: 99%
See 4 more Smart Citations
“…Studies about regulation of G6PD has been carried out in plants, eukaryotic algae and cyanobacteria but glucose-6phophate dehydrogenase encoding gene has been isolated from only few of these sources (Srivastava and Anderson, 1983;Fickenscher and Scheibe, 1986;Graeve, Schaewen and Scheibe, 1994;Gleason, 1996). Two isoforms (cytosolic and chloroplastic isoforms) of G6PD has been reported in green algae Chlorella vulgaris C-27 (Honjoh et al, 2003). Several isoforms of G6PDH have been reported in cytosol, plastidic stroma, and peroxisomes of higher plants (Corpas et al, 1998).…”
Section: Distribution Of Glucose-6-phosphate Dehydrogenasementioning
confidence: 99%
“…2",5"-ADP-Sepharose 4B affinity gel chromatography 650/31% Ciftci et al(2003) Goose erythrocyte Ammonium sulphate precipitation and 2",5"-ADP-Sepharose 4B affinity gel chromatography 3892/68.79% Beydemir et al(2003) Chlorella vulgaris C-27(Two isoforms) Hi Trap blue Column 109 and 197/- Honjoh et al(2003) Coriandrum sativum Ammonium sulphate fractionation and DEAE-Sephadex A50 ion exchange chromatography -/26.4% Demir et al 2004Rainbow trout Ammonium sulphate precipitation and 2",5"-ADP-Sepharose 4B affinity gel chromatography 1271.19/70.40% Ciftci et al 2004Goat Erythrocyte Warburg and Christian, 1937) found that the active form of protein can be obtained from Lebdev juice by acidification with carbon dioxide. Glaser and Brown made attempts for extraction and purification of brewers" yeast enzyme by ammonium sulphate precipitation, calcium phosphate gel adsorption and ethyl alcohol fractionation (Glaser and Brown, 1955).…”
Section: /18%mentioning
confidence: 99%
See 3 more Smart Citations